Facilitating Air Freight – Policies and Actions - Saslavsky, Daniel (World Bank, Washington, DC, 2020)
Air connectivity is at the center of the COVID-19 (Coronavirus) crisis. Global air cargo capacity has dropped substantially since most commercial passenger flights have been cancelled or grounded worldwide. Air cargo operators are trying to satisfy the existing demand, and also support pandemic-related relief efforts, mostly with freighters, and also with repurposed passenger widebody aircrafts (carrying freight in the main cabin). The economic impact for developing countries is likely to be felt directly through the loss of cargo capacity and skyrocketing air cargo rates, as well as cascading effects from all-cargo operations. Governments should coordinate and work with industry to ease regulatory and operational restrictions on air cargo operations to ensure market access, essential operations, and timely turnaround at airports and hubs. Many passenger airlines (responsible for hauling half of air cargo globally) will require financial support or restructuring, in a context of prolonged revenue starvation and assets’ immobility.